A Scoping Review of Disposal of Unused Medicines in Take-Back Programs - Mufti Alifia Rahmadani; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Unused medicines in the household cause many problems. Medicines take-back programs were established to prevent inappropriate medicines disposal, abuse, accidental poisoning, and help reduce the number of unused medicines in households. A literature search using the keywords “unused AND medicine”, “disposal AND unused AND medicine”, “reasons AND medicine AND disposal”, “medicine AND take-back program” and “cost AND medicine AND take-back program” in PubMed, Science Direct, Scopus and Google Scholar. Articles published in 2010 – 2020 in English report the medicine take-back program with the number of medicines and/or reasons for the return and/or economic value of medicines collected in the medicines take-back program. A total of 16 articles were included in the criteria for this systematic review. Medicines take-back program was majority-owned in the US (69%). Two programs focus on returning controlled medicines. Gastrointestinal, respiratory, cardiovascular, antimicrobial and non-narcotic analgesic were the most common of all medicines returned. The expired medicine and treatment discontinuation by (doctors/prescribers) were the most reason medicine was returned to the medicines take-back program. The total cost of all medicines returned topped $1,118,020. Medicines take-back program was an essential solution to the inappropriate medicine disposal problem. Good coordination was required between the government and other authorities.This medicine take-back issues can help solve the problems of medicine use, storage, and disposal that lead to the country's economy.